2005
DOI: 10.1007/s10038-005-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil infiltration in three patients with generalized atrophic benign epidermolysis bullosa from a Japanese family: molecular genetic and immunohistochemical studies

Abstract: Generalized atrophic benign epidermolysis bullosa (GABEB), a subtype of epidermolysis bullosa (EB), is an autosomal recessive skin disease characterized by derm-epidermal separation leading to skin fragility and atrophy and other associated abnormalities. Although a few reports demonstrated that eosinophils are infiltrating beneath bullas in infants with some types of EB, no such condition in adult GABEB patients has been known. Here we report on three adult patients with GABEB from a Japanese family, whose bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[8][9][10] Although it is tempting to postulate that the inflammatory infiltrates are responsible for the pruritus, pruritus was a prominent feature in some cases of DDEB pruriginosa in which inflammatory infiltrates were histologically absent. [8][9][10][11][12] Wally et al 13 found that the keratinocytes of patients with the Dowling-Meara subtype of EBS have constitutively activated IL-1b signalling. 13 Glial IL-1b and tumour necrosis factor-a can cause a central sensation of pain, but it is not yet known whether these cytokines activate pruriceptive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Although it is tempting to postulate that the inflammatory infiltrates are responsible for the pruritus, pruritus was a prominent feature in some cases of DDEB pruriginosa in which inflammatory infiltrates were histologically absent. [8][9][10][11][12] Wally et al 13 found that the keratinocytes of patients with the Dowling-Meara subtype of EBS have constitutively activated IL-1b signalling. 13 Glial IL-1b and tumour necrosis factor-a can cause a central sensation of pain, but it is not yet known whether these cytokines activate pruriceptive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A 41‐year‐old Japanese man presented with his entire body covered with blisters, which had started following a minor neonatal trauma. He was the child of a consanguineous couple and had two aunts with JEB‐nH 2 . The diagnosis of JEB was made at Kobe University Hospital when he was 2 years old.…”
Section: Case Reportmentioning
confidence: 99%
“…In 2004, he and his two aunts were diagnosed with JEB‐nH based on the results of genetic linkage and mutation analysis performed at Nagasaki University Hospital. A homozygous insertion mutation, 209–210insCA in exon 5 of COL17A1 encoding type XVII collagen, was detected 2 . Since 2005, he had been suffering from aggressive new blister formations after scratching caused by severe itching, accompanied by general fatigue, fever and appetite loss.…”
Section: Case Reportmentioning
confidence: 99%
“…Mechanobullous disorders and immunobullous disorders have been reported to coexist together. This finding was observed in a 56-year-old male with a clinicopathological diagnosis of junctional EB, generalized 27 3 Junctional EB Eosinophils Drury and Prieto 28 2 Dystrophic EB Eosinophils, leukocytes Ning et al 29 1 Dystrophic EB Eosinophils, neutrophils Grunwald et al 1 1 Dystrophic EB Eosinophils Vivehanantha et al 16 1 Dystrophic EB (EB pruriginosa) Eosinophils, lymphocytes Roth et al 2 24 However, an earlier case reported a 41-year-old male with junctional EB, generalized intermediate, who presented with clinical features of severe itching and eosinophilia, yet DIF was negative for bullous pemphigoid. This patient subsequently improved after treatment with oral steroids.…”
Section: Discussionmentioning
confidence: 53%